Drug Resistance of Staphylococci II. Joint Elimination and Joint Transduction of the Determinants of Penicillinase Production and Resistance to Macrolide Antibiotics - Mitsuhashi, Susumu (1965)
Mitsuhashi, Susumu (Gunma University, Maebashi, Japan), Hajime Hashimoto, Megumi Kono, and Masato Morimura. Drug resistance of staphylococci. II. Joint elimination and joint transduction of the determinants of penicillinase production and resistance to macrolide antibiotics. J. Bacteriol. 89:988–992. 1965.—Strains of Staphylococcus aureus, which show high resistance to macrolide antibiotics (erythromycin, oleandomycin, leucomycin, and spiramycin) and the capacity to produce penicillinase, have been isolated from clinical sources. The determinants of penicillinase production (PCase(+)) and resistance to macrolide antibiotics (MAC(r)) of these strains were irreversibly eliminated by treatment with acridine or with ultraviolet light. Among the 18 strains tested, PCase(+) and MAC(r) were eliminated from all strains except one, which lost only PCase(+) but not MAC(r). The characters PCase(+) and MAC(r) were jointly transduced with the aid of phage lysates, obtained from the resistant donors by ultraviolet irradiation, into staphylococcal strains sensitive to PC and MAC. Segregation of PCase(+) and MAC(r) was rarely observed after transduction. From these results, it is suggested that the determinants of both PCase(+) and MAC(r) of staphylococci are located close together on a single genetic element, i.e., a plasmid (or episome), which exists extrachromosomally.